The Case of Insertional Adductor Tendinopathy of an International-Level 3,000-m Steeplechase Runner - Ewan Thomas; Marcello Giaccone; Marcello Giaccone; Angelo Iovane; Gaspare Polizzi; Marco Petrucci; Giuseppe Messina; Antonio Palma (Frontiers Media S.A., 2021)
Background: Groin pain is a frequent condition among athletes. One of the causes of groin pain is tendinopathy, a frequently diagnosed medical condition, which can also occur in the adductor muscles. Despite the high prevalence of this medical condition among athletes, it is infrequent to observe tendinopathic groin pain in steeplechase runners. The aim of this case study is to describe the case of an international-level 3,000-m steeplechase runner with groin pain, who was subsequently diagnosed with adductor insertional tendinopathy.Case Presentation: We present the case of an Italian 3,000-m steeplechase and long distance runner, Ala Zoghlami (180 cm, 57 kg), with groin pain, diagnosed as insertional adductor tendinopathy. The runner, after manifesting the painful symptomatology, underwent medical screening (ultrasound and MRI). The radiological investigations highlighted adductor tendinopathy. After refraining from training, the runner underwent medical and physical therapy which, in the first phase, did not improve the painful symptomatology. Further evaluation, after 6 months from the initial training cessation, highlighted a case of malocclusion. Such was treated from a dentistry perspective with the creation of a personalized dental bite.Results: A multidisciplinary approach which included medical and physical therapy, osteopathy, and dentistry, in adjunct with refraining from training, was able to reduce the symptomatology and allowed a correct return to run (after 9 months from the first painful manifestation) of the steeplechase runner. To date, Ala Zoghlami has fully recovered and was able to win the 3,000-m steeplechase race during the 2021 national Italian competition.